DECIPHERING THE EFFECT OF CURRICULA ON THE PERCEPTION OF THIRD LEVEL ENGINEERING - A COMPARATIVE ANALYSIS - KELLY, KEVIN (My University, 2012)
Recent PISA surveys have shown that Ireland’s relative ranking in Mathematics has fallen sharply, while Finland maintains its posit ion at the top of the international table. Simultaneously, Ireland is experiencing a short age of engineers and falling/static demand for engineering programmes, in common wit h many Western economies, while Finland maintains both a strong public image of the p rofession and a sufficient supply of able students into university. The recent economic woes experienced in Ireland have thrown the diffic ulties in the STEM area into sharp focus, and there is, at least currently, a momentum for change in the education system. With Finland having successfully progressed through a similar crisis in the 1990s, and having transformed its education system, it s eems appropriate to examine what lessons can be learned. The structure of the education system at secondary level in both countr ies, with particular focus on the STEM area, is compared and conclusions are drawn with regard to the relative performances in the PISA scores and the public perce ption of the profession, including its effect on student recruitment.
4th International Symposium on Engineering Education
Keywords: perception; society; academic structure; economic growth; engineering education